From fields to futures: Farmer FIRST Programme transforming rural livelihoods through science and participation - Sahu, Subhashree; Satyapriya; Burman, R. R. (Indian Farming, 2025)
The Farmer FIRST Programme (FFP) of ICAR-IARI, New Delhi, has transformed farming communities in Palwal district, Haryana, through participatory technology application and multistakeholder convergence. Operating across four clusters—Amarpur, Dadhota, Katesra, and Kulena, the project integrates crop, horticulture, livestock, and enterprise-based interventions over 93.2 ha, benefiting more than 760 farm families. Demonstrations of improved wheat, paddy, and mungbean varieties enhanced productivity, profitability, and resource efficiency. Diversification through vegetables, floriculture, and nutrition-oriented kitchen gardens empowered women and improved household nutrition. Livestock health initiatives, protected cultivation, and mushroom enterprises further strengthened income resilience. Capacity-building activities and institutional convergence fostered farmer–scientist collaboration, entrepreneurship, and sustainable livelihoods. The initiative exemplifies how participatory science can drive rural transformation, blending innovation with inclusivity and environmental stewardship.